2022
DOI: 10.1186/s11658-022-00318-8
|View full text |Cite
|
Sign up to set email alerts
|

Obacunone alleviates ferroptosis during lipopolysaccharide-induced acute lung injury by upregulating Nrf2-dependent antioxidant responses

Abstract: Background Acute lung injury (ALI) has received considerable attention in the field of intensive care as it is associated with a high mortality rate. Obacunone (OB), widely found in citrus fruits, is a natural bioactive compound with anti-inflammatory and antioxidant activities. However, it is not clear whether OB protects against lipopolysaccharide (LPS)-induced ALI. Therefore, in this study, we aimed to evaluate the protective effects of OB and the potential mechanisms against LPS-induced ALI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Studies have demonstrated that natural pharmaceutical ingredients such as panaxydol and obacunone inhibit ferroptosis by activating the Nrf2/HO-1 pathway, thereby alleviating ALI. These findings reveal that natural medicine components inhibit ferroptosis by activating the Nrf2/HO-1 pathway, thus alleviating ALI ( Li et al, 2021 ; Li et al, 2022 ). These findings also provide a direction for the study of natural medicines for treating ALI caused by IIR and seawater drowning ( Table 1 ).…”
Section: The Protective Effect Of Natural Medicines On Various Acute ...mentioning
confidence: 76%
See 2 more Smart Citations
“…Studies have demonstrated that natural pharmaceutical ingredients such as panaxydol and obacunone inhibit ferroptosis by activating the Nrf2/HO-1 pathway, thereby alleviating ALI. These findings reveal that natural medicine components inhibit ferroptosis by activating the Nrf2/HO-1 pathway, thus alleviating ALI ( Li et al, 2021 ; Li et al, 2022 ). These findings also provide a direction for the study of natural medicines for treating ALI caused by IIR and seawater drowning ( Table 1 ).…”
Section: The Protective Effect Of Natural Medicines On Various Acute ...mentioning
confidence: 76%
“…Recently, several studies have shown that ferroptosis is a type of regulatory necrosis that is more immunogenic than apoptosis and exacerbates the inflammatory response of ALI. Moreover, studies have demonstrated that panaxydol and obacunone inhibit lung injury caused ferroptosis through the activation of the Nrf2/HO-1 pathway, and inhibition of the production of inflammatory factors TNF-α, IL-1β, and IL-6 in the lungs ( Li et al, 2021 ; Li et al, 2022 ). Therefore, the Nrf2 pathway activated by various types of natural medicines is involved in the prevention and treatment of septic ALI ( Table 1 ).…”
Section: The Protective Effect Of Natural Medicines On Various Acute ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sevoflurane reduces LPS-induced ALI by repressing ferroptosis via the upregulation of HO-1 expression [205]. Obacunone reduces LPS-induced ALI by suppressing ferroptosis via the increase of Nrf2dependent antioxidant responses [206]. Hydrogen sulfide reduces ferroptosis and activates autophagy by downregulating mTOR signaling in sepsis-induced ALI [207].…”
Section: Lung Diseasesmentioning
confidence: 99%
“…Ferroptosis plays an important role in many physiological and pathological processes, including development, aging, and immunity ( Stockwell, 2022 ). Ferroptosis is inseparable from the occurrence and development of various diseases, including cardiovascular diseases, neurological degenerative diseases, cancers, ischemic organ injuries, endocrine diseases, and respiratory diseases ( Hu et al, 2019 ; Li et al, 2022a ; Fang et al, 2022 ; Lin et al, 2022 ; Qu et al, 2022 ; Stancic et al, 2022 ; Zhang and Li, 2022 ). Iron accumulation, phospholipid peroxidation, and amino acid, lipid, and sugar metabolism are the most important components of ferroptosis ( Jiang et al, 2021 ).…”
Section: Introduction and Brief Historymentioning
confidence: 99%